The Legacy of Sport Events for Emerging Nations - Brendon Knott; Cem Tinaz (Frontiers Media S.A., 2022)
Large-scale and mega sport events (SMEs), such as Olympic Games and FIFA World Cups, have been more frequently hosted in emerging nations. Bidding and hosting SMEs is considered an object of policy for many emerging nations, with SMEs viewed as key factors in local and national development strategies. This has largely been driven by the assumption that their legacy provides solutions to economic, social, cultural, or political challenges. A variety of legacies have predominated the literature over the past two decades, however it is proposed that there is a difference in the types of legacies anticipated or realized within emerging nations. This exploratory study therefore aimed to determine the types of legacies anticipated or realized by emerging nations as a result of hosting sport events, and to determine if these differ from those of established nations. A systematic literature review followed the PRISMA approach to identify and select peer-reviewed articles that focused on legacies from major and mega-events hosted in emerging nations. A set of 97 publications were analyzed qualitatively to reveal the key legacy themes. The findings confirm legacy as a growing body of knowledge in emerging nations, aligned with increasing event hosting. The findings reveal insights on the extent of literature on this topic in emerging nations, including the major nations, events, authors and publications represented. While the paper cannot determine unique legacies for emerging nations, it identifies key legacy focus areas for these nations, primarily: social development; politics, soft-power and sport-for-peace; the economics of tourism, image and branding; infrastructure and urban development; and sport development. This paper proposes a conceptualization of key legacy areas for emerging nations and proposes future research themes. The paper is unique in its highlighting of the significance of legacy outcomes for emerging nations from the hosting of sport mega-events. It therefore contributes to a more nuanced understanding of and imperative for legacy from sport events globally.